LAPORAN PRAKTIKUM EKOSISTEM - Dewi Ratna Sari; Nurul Hasanah (CV. KAMPUS AKADEMIK PUBLISING, 2025)
This practicum aims to identify biotic and abiotic components in an ecosystem , observe the relationships between ecosystem components , and develop skills in creating a simple model of a closed ecosystem. The experiment was conducted by creating a mini ecosystem in a bottle (simple terrarium) using a clear plastic bottle/jar, soil, gravel, moss/small leaves/wild grass, and water. Observations showed that the terrarium ecosystem can function independently with an automatic water cycle occurring through evaporation and condensation. The balance between biotic components (plants as producers) and abiotic components (soil, water, light) is crucial for the system's sustainability. This practicum provides a concrete understanding of interdependency within ecosystems and the importance of maintaining environmental balance.